ANALYSIS OF THE EFFECTIVENESS OF STEM-BASED PjBL MODEL TO DEVELOP STUDENTS' CREATIVITY - Carsono, Adi; Heliawati, Leny; Permana, Irvan (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2025)
This study aims to analyze the effectiveness of the STEM-based Project-Based Learning (PjBL) model in improving students' scientific creativity on the topic "Separation of Mixtures" in class VIII of SMP Negeri 36 Jakarta. The background of this study departs from the need for science learning that is able to foster creativity and critical thinking through contextual and collaborative experiences. The method used is a quasi-experimental with a pretest-posttest non-equivalent control group design, involving two classes of 36 students each. The experimental class used the STEM-based PjBL model, while the control class applied the Discovery Learning model. Data were collected through creative thinking skills tests and analyzed with SPSS. The results showed a significant increase in students' creativity scores in the experimental class (p = 0.000) with a large to very large effect size based on Cohen's d calculation and Hedges' correction. These findings indicate that STEM-based PjBL has a strong practical effect in developing students' scientific creativity. In conclusion, the implementation of STEM-based PjBL is effective in improving creative thinking skills through contextual, collaborative, and challenging learning, and contributes to strengthening the science education approach that is oriented towards developing 21st-century competencies.